Faktor-Faktor Yang Mempengaruhi Minat Usaha Mikro Kecil Menengah Menjadi Nasabah Pembiayaan Di Lembaga Keuangan - RACHMAWATI, NINDA; ANI PRAYEKTI, ROSI (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
Financial institutions have an important role in the economy of a country, namely as financial intermediary institutions. The types of financial institutions in Indonesia are divided into two types, namely those differentiated based on interest payments, conventional financial institutions (LKK) or profit sharing, and sharia financial institutions (LKS). The growth of Sharia financial institutions will be faced with competition between conventional bank interest rates and the profit-sharing rates received by customers. This competition will lead to the choice factors of the Indonesian people in investing or making transactions. Many people choose to invest in conventional financial institutions because they see the high interest rates offered. This research aims to find out whether the level of trust, service, return of results, and compliance with Sharia law influence the decision of micro, small, and medium enterprises to become financing customers at conventional financial institutions and Sharia financial institutions. The sampling technique uses a probability sampling method or random sample selection. The respondents in this research were Micro, Small, and Medium Enterprises (MSMEs) in Godean District, Sleman Regency, Yogyakarta Special Region Province. Data analysis of factors that differentiate MSMEs into LKK and LKS customers was processed using SPSS 21.0 for Windows. The conclusion is that the level of trust, level of service, level of returns, and level of legal compliance influence the decision of micro, small, and medium enterprises to become customers in conventional financial institutions and sharia financial institutions.